When It Rains, It Pours: Integrating Citizen Science Methods to Understand Resilience of Urban Green Spaces - Pudifoot, Bethany; Cárdenas, Macarena L.; Buytaert, Wouter; Paul, Jonathan D.; Narraway, Claire L.; Loiselle, Steven (Frontiers in Water, 2021)
Urban green spaces are often promoted as nature-based solutions, thus helping to mitigate the negative effects of climate change. Estimating the potential environmental benefits provided by urban green space is difficult because of inconsistencies in management practices and their heterogeneous nature. Collecting data across such a spectrum of contexts at a large scale is costly and time consuming. In this study, we explore a novel integrated method for citizen scientists to assess the flood mitigation potential of urban green spaces. In three European cities, citizen scientists measured infiltration rate and associated soil characteristics in managed and unmanaged urban green spaces. The results show that simple citizen science-based measurements can indicate the infiltration potential (i.e. high vs. low) of soil in these sites. Infiltration rate was best predicted by measurements of soil compaction, soil colour, air temperature and level of insolation (i.e. high vs. low). These simple, fast methods can be repeated over time and space by citizen scientists to provide robust estimates of soil characteristics and infiltration potential of soils existing in similar temperate urban areas. A classification flow diagram was constructed and validated that allows citizen scientists to carry out such tests over a wider geographical region and at a higher frequency than would be available to research scientists alone. Most importantly, it allows citizens to take actions to improve infiltration in their local green space and support local flood resilience.